1992
DOI: 10.2307/1131558
|View full text |Cite
|
Sign up to set email alerts
|

Some Consequences of Early Harsh Discipline: Child Aggression and a Maladaptive Social Information Processing Style

Abstract: Although a number of studies have reported a relation between abusive parental behavior and later aggressive behavior in the victim, many of these investigations have had methodological limitations that make precise interpretation of their results problematic. In the present study, we attempted to determine whether harsh parental discipline occurring early in life was associated with later aggression and internalizing behavior in children, using a prospective design with randomly selected samples to avoid some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
255
3
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(284 citation statements)
references
References 0 publications
17
255
3
8
Order By: Relevance
“…Indeed, if we excluded data of these children from the multivariate analysis, the difference between bullies and bully‐victims became nonsignificant. It is possible that these children's extreme scores were outliers or stemmed from home experiences such as harsh parenting (Weiss, Dodge, Bates, & Pettit, 1992). However, these interpretations are quite speculative and further research seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if we excluded data of these children from the multivariate analysis, the difference between bullies and bully‐victims became nonsignificant. It is possible that these children's extreme scores were outliers or stemmed from home experiences such as harsh parenting (Weiss, Dodge, Bates, & Pettit, 1992). However, these interpretations are quite speculative and further research seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Some additional evidence suggests that the age range between 9 and 12 has been linked to a number of variables including decreases in parental monitoring and increases in the hostility of the school environment, child autonomy within the school environment, and peer influence on children (Blyth et al, 1978;Eccles et al, 1993;Fite et al, 2006). Research has indicated that the role of peer influence on children also shows a curvilinear pattern in which children's conformity with their peers peaks during the middle-school years (Berndt, 1979 (Leff et al, 2006;Lochman & Dodge, 1994;Weiss, Dodge, Bates, & Pettit, 1992). In these media, short social interactions, or vignettes, are presented visually to the participant.…”
Section: Reactive Vs Proactive Aggressionmentioning
confidence: 99%
“…Some of the cartoon-based measures have coupled visual stimuli with a narrative story read aloud to participants that describes what is happening in the depiction (Leff et al, 2006;Weiss et al, 1992). Narrative stimuli have also been used alone as auditory stimuli.…”
Section: Reactive Vs Proactive Aggressionmentioning
confidence: 99%
See 2 more Smart Citations